Ramadan Da'wah Safari in Improving Motivation to Learn the Qur'an - Tumanggor, Ilham; Abdul Raafi; Muhammad Riannur Hidayah (ASSUNNAH PRESS, 2023)
Sidoharjo I Pasar Miring Village is located in Pagar Merbau Sub-district, Deli Serdang Regency, North Sumatra Province. This village has a majority Muslim population. Mosques are also built evenly throughout the village as a place that supports worship and religious activities. In general, the people of Sidoharjo I Pasar Miring Village have a religious attitude, a spirit of worship, hard workers with open minds. However, based on the observations of the KKN team, the phenomenon of children's low ability to read the Koran correctly and the low motivation of children in learning the Koran were found. The Participatory Action Research (PAR) approach was used to overcome the existing problems and develop children's motivation to continue learning the Quran. Tahsin activities, learning Iqra' and tahfizh with interesting methods are expected to provide significant changes to children who cannot read the Koran or still stammer in reading the Koran and improve the quality and quantity of children's memorisation. The activities carried out for 15 days can be said to be successful in improving the quality of children's reading and memorisation of the Quran and motivating them to continue learning the Quran.